2019
DOI: 10.1111/dth.12820
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of lipedema by low‐volume micro‐cannular liposuction in tumescent anesthesia: Results in 111 patients

Abstract: Lipedema is a painful disease of subcutaneous adipose tissue leading to bilateral increase of leg and/or arm volume, but sparing hands and feet. Although conservative treatment with complex decongestive therapy has been considered as the fundamental treatment, micro‐cannular liposuction in tumescent anesthesia has become a surgical option. We report on 111 patients mostly with advanced lipedema treated by this technique in our center between 2007 and 2018. The median age of the patients was 44 years. Eighty pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 29 publications
2
78
0
7
Order By: Relevance
“…With careful patient selection, several observational studies indicated that the surgical therapy was able to improve lipedemaassociated symptoms (pain perception, tension sensation, hematoma tendency, quality of life) as well as objectively measurable parameters such as leg circumference or extent of conservative therapy. [21][22][23][24][25] The results of this retrospective analysis underline this data. In addition, an improvement in menstrual irregularities could be observed.…”
Section: Surgical Outcome On Lipedema Symptomssupporting
confidence: 60%
See 2 more Smart Citations
“…With careful patient selection, several observational studies indicated that the surgical therapy was able to improve lipedemaassociated symptoms (pain perception, tension sensation, hematoma tendency, quality of life) as well as objectively measurable parameters such as leg circumference or extent of conservative therapy. [21][22][23][24][25] The results of this retrospective analysis underline this data. In addition, an improvement in menstrual irregularities could be observed.…”
Section: Surgical Outcome On Lipedema Symptomssupporting
confidence: 60%
“…1,20 Randomized controlled studies on the benefits of liposuction for lipedema are currently not available, but a number of selected observation studies have described evidence of permanent symptom reduction by removal of the pathological adipose tissue. [21][22][23][24][25] Furthermore, a reduction of menstrual disorders after surgical treatment has been reported. 5 Current publications have described a large number of associated comorbidities for patients with lipedema.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…They described a median total amount of lipoaspirate of 4,700 mL, a median reduction of limb circumference of 6 cm, and a median pain level lowering from 7.8 to 2.2 at the end of treatment as well as improved mobility and bruising. Serious adverse events were observed in 1.2% of procedures, with infection and bleeding rates being 0% and 0.3%, respectively .…”
Section: Treatmentmentioning
confidence: 99%
“…Moreover, no serious complication occurred following the procedure, with wound infection rates of 1.4% and bleeding rates of 0.3% . Very recently, Wollina et al reported on 111 patients mostly with advanced lipedema treated by microcannular liposuction in tumescent anesthesia between 2007 and 2018. They described a median total amount of lipoaspirate of 4,700 mL, a median reduction of limb circumference of 6 cm, and a median pain level lowering from 7.8 to 2.2 at the end of treatment as well as improved mobility and bruising.…”
Section: Treatmentmentioning
confidence: 99%